2018
DOI: 10.1590/1678-5150-pvb-5504
|View full text |Cite
|
Sign up to set email alerts
|

Doenças podais em ovinos no estado da Bahia

Abstract: RESUMO: As doenças dos cascos são as principais causas de claudicação em pequenos ruminantes, causando grande impacto no bem-estar dos animais e provocando sérias perdas econômicas com depreciação e abate de animais afetados. O objetivo do presente estudo foi determinar a ocorrência e caracterizar as doenças podais encontradas em oito rebanhos de ovinos com histórico de doenças podais pertencentes a oito municípios do estado da Bahia. Em cada visita, foram realizadas inspeções do rebanho, aplicação de um quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Even though the general prevalence of foot lesions herein described is similar to other studies (Aguiar et al 2011, Carvalho et al 2018, the great differences consists in the proportion of each foot disease. WLD was the most observed lesion, but other studies found the highest prevalence of footrot followed by interdigital dermatitis (Aguiar et al 2011, Carvalho et al 2018. This difference may be related with the prophylactic measures carried out on the farm, including footrot vaccination.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Even though the general prevalence of foot lesions herein described is similar to other studies (Aguiar et al 2011, Carvalho et al 2018, the great differences consists in the proportion of each foot disease. WLD was the most observed lesion, but other studies found the highest prevalence of footrot followed by interdigital dermatitis (Aguiar et al 2011, Carvalho et al 2018. This difference may be related with the prophylactic measures carried out on the farm, including footrot vaccination.…”
Section: Discussionsupporting
confidence: 81%
“…It should be noted the cases of footrot occurred three times less than the cases of interdigital dermatitis, indicating that the use of footrot vaccine is of great value to reduce the incidence of this disease, as well as also may improve the recovery of affected animals (Duncan et al 2012). Even though the general prevalence of foot lesions herein described is similar to other studies (Aguiar et al 2011, Carvalho et al 2018, the great differences consists in the proportion of each foot disease. WLD was the most observed lesion, but other studies found the highest prevalence of footrot followed by interdigital dermatitis (Aguiar et al 2011, Carvalho et al 2018.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations